Statistical Analysis of Reinforced Concrete Bridge Defects for Optimum Maintenance Planning and Budgeting - Abdul-Ameer, A. (2016)
Concrete degradation is arguably the main restriction on longevity of service life of buildings and infrastructure, most developed economies spend more on rehabilitation of existing structures than on new one. Concrete can be damaged by a range of chemical , physical and biological cause that include; fire, sea water, aggressive environment, corrosion of reinforcement, impact, bacterial attach to name a few. There is a continuing argument about the main cause of the premature deterioration of structures containing reinforced concrete, these range from inadequate specification, poor design and detailing, poor workmanship and aggressive environment. By far the biggest cause of deterioration is the corrosion of the steel reinforcement, with its expansive byproducts that result in the cracking and spilling of concrete and can ultimately cause total service life failure of the structure if not checked and remedied. Maintenance engineers face an ever ending problem of when is the optimum time to intervene and rehabilitate a deteriorated structural element or whole structure. Budget restrictions and need to optimize the maintenance cycle. The paper will report on a large database of deterioration records of concrete bridges covering a period of over 60 years and include data from over 400 bridge structures. Statistical analysis were used to estimate the deterioration rates of various reinforced concrete defects in a rage of structural elements and bridge types and to arrive a mean service life oreinforced of the structure, such service life data can then be used by the maintenance manager to budget and prioritize his maintenance work.